Study On Identity-Based Identification Schemes - Chin, Ji Jian (2008)
The author begin with a through surbey of existing identity-based identification (IBI) schemes in literature. Then introduce some background information on IBI such as hard mathematical problems IBI schemes are built from, the formal definition and security models for IBI, transformations that IBI schemes are derived from, recent developments in IBI and conclude with a tabulated summary of all known IBI schemes in literature.